OPTIMIZATION OF ASSESSMENT OF RISKS AND NEEDS OF PRISONERS IN THE IMPLEMENTATION OF THE INDEPENDENCE DEVELOPMENT PROGRAM IN CLASS IIA COMMUNITY INSTITUTIONS PEMATANG SIANTAR BENGKULU - Alfiqri, Syahrun; Equatora, Muhammad Ali; Muhammad, Ali (TOPLAMA, 2024)
In social life, children's development tends to be in the spotlight because children are predicted to be the next generation who are the hopes of parents, families, religion, and even the state. Concerns about a child's future arise when a child comes into conflict with the law due to a criminal act he or she has committed and is serving a prison term. However, these concerns were dispelled by the presence of legislation which ensured that this country paid more attention to its human resources. This research aims to produce a service based on a humanistic approach carried out by correctional officers for assisted children, where later this service can become a forum for developing children during their criminal period as well as preparing children for a better life after the criminal process is completed. This study used qualitative research methods. By taking a humanistic concept which refers to basic needs, security needs, social and affection needs as well as self-actualization needs which will later be applied to the Class IIA Bengkulu Special Development Institute for Children.